The UN Security Council and International Terrorism (Polish Yearbook of International Law, 2021)
The present contribution pays tribute to the late Professor Janusz Symonides by examining the position of United Nations Security Council towards international terrorism. The analysis concentrates on how the phenomenon is perceived by the main political organ of the United Nations, and offers some cursory remarks on its reactions (both actual and potential).